Digging deeper for benefits: rural local governance and the livelihood and sustainability outcomes of devils claw (Harpagophytum spp.) harvesting in the Zambezi Region, Namibia - Lavelle, Jessica-Jane (Department of Environmental and Geographical Science, 2020)
Natural resource governance in Africa is characterised by increased commercialisation of natural resources, the promotion of community-based natural resource management, and a re-appropriation of traditional authorities and customary law as evidenced by their inclusion in statutory frameworks. Yet, knowledge of the interaction and effect of these multiple governance arrangements on local communities is limited. Using the lens of devil’s claw (Harpagophytum spp.), a commercial non-timber forest product, this research examines the interface between statutory, traditional and comanagement governance systems; the broader historical and political-economic contexts that shape governance systems; livelihood and sustainability outcomes at the local level; and the role of power in determining environmental, social and economic outcomes. The research adopted a case study method with three study sites selected in the Zambezi Region, Namibia – Balyerwa Conservancy, Lubuta Community Forest and Sachinga. All rural communal areas, selection was based on their distinct governance arrangements, including a range of traditional and co-management institutions, development interventions and statutory regulation. Qualitative methods were used and included questionnaires, focus group discussions, interviews, participant observation and documentary evidence. An institutional mode of analysis and a political ecology approach were applied. Theoretical perspectives to inform the research were drawn from discourses on governance, institutions, political ecology, power and access. The novelty in using a political ecology approach to develop adaptive governance theory was to move beyond understandings of the conscious mechanisms of institutions embodied in their structure, to a more nuanced understanding of socially-embedded institutions and the unconscious mechanisms that also determine social and environmental outcomes. The empirical knowledge gained from this research shows that both structural and socially-embedded institutional constraints are hindering the objectives of non-timber forest product governance. The results of this research affirm that governance is hybridising and that dichotomised descriptions of governance as customary or statutory, self-organising or hierarchical, do not capture the complexity of these evolving fusions of governance at the local level. Where a multiplicity of institutions existed at the local level, the role of the State was diminished and where co-management was in place, communities benefited from non-governmental organisation support which enabled greater benefits for harvesters and more sustainable practices. However, power was not restructured under such arrangements and differentials in access, knowledge, decision-making and benefits remained. Where co-management was not in place, harvesters were not supported in their harvesting activities and were most vulnerable to exploitation by traditional leaders and buyers. This exacerbated competition over the resource and unsustainable harvesting was more prevalent. Devil’s claw was used as a traditional medicine by some members of these communities but did not hold significant socio-cultural value. Customary systems of management for devil’s claw were therefore weak or absent and oversight of the resource was perceived to be the jurisdiction of the State. Statutory regulation of devil’s claw was however found to be ineffective; when in place, the State perceived the co-management institutions to be responsible for monitoring and evaluation. The implementation of quotas, traceability and better pricing from exporters exerted a greater influence than regulation in promoting sustainability. In the absence of non-governmental support and exporters adhering to quotas, unsustainable harvesting prevailed. A central finding is that alteration, the bending or breaking of rules by local communities, is a strategy to cope with economic precariousness that is inflicted by broader political-economic conditions. This affirms the need for an alternative economic logic to be examined that incorporates non-timber forest products into diverse agroforestry production systems that stimulate markets within rather than external to localities and draws on existing cultural practices and preferences to shape landscapes and economies in more holistic, equitable ways. The research concludes that benefits for harvesters and the sustainability of devil’s claw are currently hindered by institutional complexity, overlapping mandates, insufficient value of the resource at the local level and a failure to instil harvester autonomy. To address these structural and sociallyembedded institutional constraints severalrecommendations are made. First, to shift co-management from decentralisation to bottom-up democratisation by devolving authority, not just responsibility, to the resource users themselves. By enabling the freedom to experiment, socially-embedded institutional constraints such as dominant narratives of ‘traditional’ and ‘uneducated’ that perpetuate unproductivity and disincentivise learning can be reframed. Second, to remove unnecessary and inefficient bureaucratic layers through re-evaluating the social scale at which natural resource management would work best and scale-up in responsibility as required to match ecological and functional scale. This would diffuse the decision-making power of the traditional authorities and the ineffectiveness of the State in communal areas whilst maintaining a role for these institutions. Lastly, to enhance market transparency to promote the mutually beneficial and regulating role between harvesters and exporters, and to emphasise the commercialisation of non-timber forest products with socio-cultural value, robust customary systems of management and local markets. The objective is not to eliminate statutory governance in favour of customary governance, nor to denounce traditional authorities in favour of co-management institutions, but to democratise power in brokering new invited spaces of modern rural governance. This study contributes to governance theory by conceptualising a framework that addresses the structural and socially-embedded institutional constraints hindering adaptive governance of NTFPs and which offers an operational solution to balance power in a bottom-up process of democratisation where legal pluralism is prevalent.